1999
DOI: 10.1002/hep.510290410
|View full text |Cite
|
Sign up to set email alerts
|

Novel Recurrent Genetic Imbalances in Human Hepatocellular Carcinoma Cell Lines Identified by Comparative Genomic Hybridization

Abstract: To search for recurrent and specific genomic alterations in human hepatocellular carcinoma (HCC), we examined 18 cell lines by comparative genomic hybridization (CGH), a molecular cytogenetic approach that allows positional identification of gains and losses of DNA sequences of the entire tumor genome. We report here a distinct pattern of multiple recurrent DNA copy-number gains and losses that include alterations frequently seen in other neoplasias as well as changes potentially specific for HCC. The most fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
3

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 53 publications
6
90
3
Order By: Relevance
“…HCC cell lines are useful material for study of hepatocarcinogenesis as an in vitro model. The frequent gains of 1q, 7, 8q, 17q, and 20q and the frequent losses of 1p, 4q, 8p, 13q, 16q, 17p, and Y were observed in HCC cell lines [11,15,16]. These results suggest the existence of oncogenes and/or tumor suppressor genes on these chromosomal regions that play an important role in hepatocarcinogenesis.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…HCC cell lines are useful material for study of hepatocarcinogenesis as an in vitro model. The frequent gains of 1q, 7, 8q, 17q, and 20q and the frequent losses of 1p, 4q, 8p, 13q, 16q, 17p, and Y were observed in HCC cell lines [11,15,16]. These results suggest the existence of oncogenes and/or tumor suppressor genes on these chromosomal regions that play an important role in hepatocarcinogenesis.…”
Section: Introductionmentioning
confidence: 81%
“…In the present study, we investigated 5 Korean HCC cell lines and found that gains of genomic material were common on chromosome 7 and chromosome regions 1q and 8q and losses on 4q, 16q, and the Y chromosome (Tables 1 and 2). Previously reported chromosomal studies on primary HCC tissues and HCC cell lines have suggested that the frequent structural abnormality at 1q is involved in HCC [15,16,26,27]. Increases in copy numbers of the LAMC2, TGFB2, and AKT3 genes at 1q have been reported in 19 HCC tissues by CGH array [28].…”
Section: Discussionmentioning
confidence: 99%
“…The new technique described in this study employs results obtained by CGH (4,13,14). Even in well-differentiated HCC, numerous recurrent aberrations have been found (2).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the time and effort required for conventional cytogenetics, this technique is usually not appropriate. The recently developed comparative genomic hybridization (CGH) has revealed promising results (2,4,11,13,14), but it is also of limited value because of the duration and amount of tissue required. By contrast, fluorescence in situ hybridization (FISH) yields results that are evaluable by simple counting of fluorescence signals in conventional biopsies (12).…”
mentioning
confidence: 99%
“…All these markers are located at chromosomal regions showing little DNA copy number variations in HCC samples. [21][22][23][24] A 21-bp oligomer complementary to the microsatellite CA repeat (5 0 FAM-ACA CAC ACA CAC ACA CAC ACA-TAMRA) was used as the probe for the reference pool. All primer pairs were tested for PCR efficiency individually and demonstrated >90% efficiency using the 10.5 CA repeat probe.…”
Section: Quantitative Microsatellite Analysismentioning
confidence: 99%